2016
DOI: 10.1080/00401706.2015.1027068
|View full text |Cite
|
Sign up to set email alerts
|

Compressing an Ensemble With Statistical Models: An Algorithm for Global 3D Spatio-Temporal Temperature

Abstract: One of the main challenges when working with modern climate model ensembles is the increasingly larger size of the data produced, and the consequent difficulty in storing large amounts of spatio-temporally resolved information. Many compression algorithms can be used to mitigate this problem, but since they are designed to compress generic scientific data sets, they do not account for the nature of climate model output and they compress only individual simulations. In this work, we propose a different, statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 50 publications
(48 reference statements)
0
46
0
Order By: Relevance
“…Statistical models can provide appropriate stochastic approximations of the spatio-temporal characteristics of the model output, and hence they can be used as surrogates of the original runs (Mearns et al, 2001). Castruccio and Stein (2013), Castruccio and Genton (2014), Castruccio and Genton (2016), and Castruccio and Guinness (2017) introduced a Stochastic Generator (SG) for annual temperature data to investigate internal variability for different ensembles, assuming that the observed ensemble members were realizations of an underlying statistical model. This approach allowed them to generate runs that were visually indistinguishable from the original model output.…”
mentioning
confidence: 99%
“…Statistical models can provide appropriate stochastic approximations of the spatio-temporal characteristics of the model output, and hence they can be used as surrogates of the original runs (Mearns et al, 2001). Castruccio and Stein (2013), Castruccio and Genton (2014), Castruccio and Genton (2016), and Castruccio and Guinness (2017) introduced a Stochastic Generator (SG) for annual temperature data to investigate internal variability for different ensembles, assuming that the observed ensemble members were realizations of an underlying statistical model. This approach allowed them to generate runs that were visually indistinguishable from the original model output.…”
mentioning
confidence: 99%
“…Castruccio and Stein () showed that such structure can be used to perform inference on massive data sets from computer model ensembles (in the range of 10 7 to 10 9 data points) by first estimating the spectrum frakturffalse(k;ϕfalse) for each of the N ϕ latitudinal bands in parallel, and then conditionally estimating the structure of the spectral correlation ρ ( k ; ϕ , ϕ ′ ). This approach has been extended to analyse three‐dimensional temperature profiles in a regular grid for a data set larger than one billion data points, allowing for an extension of axially symmetric models in three dimensions (Castruccio & Genton, ).…”
Section: Practical Approachesmentioning
confidence: 99%
“…The headset is equipped with a wireless motion capture device to allow each user to explore the data within the environment interactively. In a recent workshop, a model for three‐dimensional temperature was fitted and simulations from a statistical model (or emulator ; full model details are given in Castruccio and Genton ()) were compared with the original climate model. An interactive display was shown.…”
Section: Beyond the Euclidean Space: Diagnostics For Three‐dimensionamentioning
confidence: 99%